Thinking with thinking with theory in qualitative research - Marn, Travis M. (Thinking, 2015)
Keywords: dept.cur

Adoptive Parents’ Suspicion and Coping With the Possibility of Child Abduction for International Adoption in China - Marn, Travis M.; Tan, Tony Xing (The Family Journal, 2015)
In this study, we investigated (1) whether adoptive parents suspected their children might have been victims of abduction for adoption in China and (2) for parents who were uncertain if their own children might be victims of child abduction for adoption, how they coped with the possibility. A total of 342 adoptive parents (representing 529 adopted Chinese children) completed an anonymous online survey on their experiences. Of the 342 parents, 154 (45%) described how they coped with the possibility that their children might be the victims of child abduction for adoption. In terms of suspicion, we found that for about 70% of the children, the parents responded Never; for 18.5% of the children, the parents responded Rarely; for 11.7% of the children, the parents responded Sometimes; and for about 1% of the children, the parents responded that they Always suspected that their children might be victims of abduction for adoption. In terms of coping with the possibility that their children might have been victims of child abduction for adoption, thematic analysis on the 154 parents’ descriptions revealed that parents experienced one or more of seven emotional reactions: sadness, frustration/helplessness, complicity/guilt, anger, fear/worry, hypervigilance, resolve, as well as the belief that they were not affected. Finally, we discussed contributing factors to child abduction for adoption and to adoptive parents’ suspicion of such a practice.
Keywords: dept.cur

Biracial Place Walkers on Campus: A Trioethnography of Culture, Climate, and Currere - Agosto, Vonzell; Marn, Travis; Ramirez, Rica (International Review of Qualitative Research, 2015)
Send this e-mail to Rica and Travis: Rica and Travis, I wish you could have been at the duoethnography panel. The first presentation had some uneasy conversations. The second, Dr. Colomer's presentation, was cool: A performance with guest actors had some sad moments with death, health issues, and attrition. The next presentation was about miscarriage and grief counseling. I wondered if our paper is frivolous in comparison to the others. I think not. Our episodes of cultural starvation and indifference are there and painful, but our comebacks are so quick (nourishment as resistance), and therefore so is the celebration. Written by Agosto while flying home after presenting at the 2014 International Congress of Qualitative Inquiry.
Keywords: dept.cur

Implicit Attitudes of International and American Adult Students toward Black and White Teachers - Na, Eunkyung; Tan, Tony X.; Marn, Travis; Ramirez, Rica (Commission for International Adult Education, 2015)
The purpose of this study was to examine hidden prejudice in two groups of adult students, international and American, against black compared to white teachers. Social desirability in the minds of participants may affect the result of a study involving racial bias (Mullins, 1982). For this reason, the researchers created a computer protocol using the standard Implicit Association Test (IAT) to measure the implicit attitudes of participants. The IAT relies on the idea of automatic information process within the mind that is not impacted by social desirability. A clear concern in education is that the racial bias toward minority students will let those implicit biases affect the way they teach those students, creating a self-fulfilling prophesy of poor student performance. But the implicit bias can work both ways and can impact a teacher's effectiveness. Traditional racial prejudice theories usually looked at white's attitudes toward blacks and other groups. This study had a significant directional shift by focusing on the international students' racial attitudes toward black and white teachers. The implicit racial attitudes of international students were also compared to those of American students. The result and evaluation of this study may be a valuable tool to improve student services and teacher professional development in higher education. Suggestions for future research are also provided.[For full proceedings, see ED570489.]
ERIC Number: ED570505
Keywords: Adult Students; African American Teachers; Attitude Measures; College Students; Comparative Analysis; Foreign Students; Gender Differences; Racial Attitudes; Racial Bias; Social Desirability; Statistical Analysis; Student Attitudes; Surveys; Whites; dept.cur

Adopted children's country of origin and post-adoption parent–child relationship quality: Findings from the United States National Survey of Adoptive Parents (NSAP) - Tan, Tony Xing; Major, Deborah; Marn, Travis; Na, Eunkyung; Jackson, Andrea L. (Children and Youth Services Review, 2015)
In this paper, we investigated adoptive parent–child relationship quality as a function of the adopted children's country of origin, pre-adoption adversity, age at placement, age, gender, and special healthcare needs status. From the 2007 National Survey of Adoptive Parents (NSAP; N=2089), we identified 1906 families that had adopted children from the US foster care system, US private agencies, China, Guatemala, Russia and South Korea. Regression analysis showed that when country of origin was the sole predictor, adoption from the US private agencies (β=.18, p<.001), China (β=.21, p<.001), Russia (β=.06, p<.05) and South Korea (β=.07, p<.05) predicted higher parent–child relationship quality score than adoption from the US foster care system (referent) (R2=5.59%). Adoption from Guatemala was not different from adoption from the US foster care system in parent–child relationship quality (β=−.01, p>.10). In the absence of country of origin, being a boy (β=−.10, p<.05), older age at placement (β=−.20, p<.001), older age (β=−.11, p<.001), having special healthcare needs (β=−.19, p<.001), and more pre-adoption adversity (β=−.08, p<.05) all significantly predicted lower parent–child relationship quality scores (R2=17.56%). When country of origin and the above variables were entered into the regression model simultaneously, being a boy, age at placement, age, and special healthcare needs status remained significant. However, none of the countries of origin except China (β=.07, p<.05) remained significant in predicting higher parent–child relationship score. Our findings showed that the unique circumstances that fueled the availability of children from different countries to become available for adoption played some role in parent–child relationship quality. However, the adopted children's gender, age at placement, age, and special healthcare needs were more predictive of post-adoption parent–child relationship quality.
Keywords: Adoption; Country of origin; Parent–child relationship quality; dept.cur